Effects of cryogenic freezing upon lithium-ion battery safety and component integrity. (July 2023) - Sunderlin, Nathaniel; Colclasure, Andrew; Yang, Chuanbo; Major, Joshua; Fink, Kae; Saxon, Aron; Keyser, Matthew
Abstract: Recycling capacity for lithium-ion batteries (LIBs) has not kept pace with the increase in battery manufacturing throughout the early 21st century. Cost-effective recycling practices must be developed to accommodate the pending influx of battery waste over the coming decades as the first generation of LIBs reach their end-of-life (EOL). Cryogenically freezing LIBs can passivate them against abusive conditions, and may therefore enable LIBs to be granted exemptions for certain hazardous material transportation requirements, significantly reducing the cost of their transportation to recycling facilities. This work aims to identify potential risks of a cryogenic transportation scenario to inform the development of standards and practices thereof. Results are presented from freeze/thaw experiments using liquid nitrogen to freeze LIBs to −197 °C. Cells are opened after thawing to assess structural damage to the cell components inherent to the freezing process. Additionally, nail penetration tests are performed on cells as they thaw to room temperature. LIBs appear undamaged after cryogenic freezing. Nail penetration experiments indicate that thermal runaway is forestalled at low temperatures, but will ensue after sufficient thawing. No thermal response was detected in cells penetrated at or below −80 °C, which approximates the melting point of the electrolyte, suggesting that LIBs are inert while the electrolyte remains frozen. Highlights: Lithium-ion battery components withstand cryogenic freezing/thawing. Thermal runaway is delayed at low temperatures (≤−60 °C). Self-heating following low-temperature nail penetration appears related to ionic conductivity. No observed thermal response to nail penetration below electrolyte freezing point